Nanoscale Structural and Chemical Properties of Ferroelectric Aluminum Scandium Nitride Thin Films - Musavigharavi, Pariasadat; Meng, Andrew C; Wang, Dixiong; Zheng, Jeffery; Foucher, Alexandre C; Olsson, Roy H; Stach, Eric A (Journal of physical chemistry. C, 2021)
The local atomic structure and nanoscale chemistry of ferroelectric aluminum scandium nitride thin films (Al1–x Sc x N) are examined using advanced transmission electron microscopy (TEM) techniques. An Al1–x Sc x N (x = 0.36) film of ∼20 nm thickness was grown on a Pt(111)/Ti/SiO2/Si(100) substrate via pulsed DC co-sputtering. Here, we describe how the Sc alloying concentration and strain distribution through the AlScN film thickness become more pronounced in ultrathin films. The homogeneous distribution of scandium and the formation of defects in the epitaxial growth of 2.1% lattice-mismatched AlScN on Pt are reported. In this paper, the “four-dimensional scanning TEM” (4D-STEM) technique is employed to systematically investigate the nanoscale order by measuring the average spacing between atoms within certain regions in the film and determining the strain. The strain map confirms a significant increase in the out-of-plane component of the lattice parameter (∼9%) at the AlScN/Pt interface. The lattice parameter in the Pt template decreases as a function of distance from the Pt/Si interface. The study of the atomic crystal structure and the chemical composition of the AlScN thin film provides useful understanding toward the applications of this material in ferroelectric memories and microelectromechanical systems.